Surgical Management of Small Bowel Crohn's Disease - Chandrasinghe, Pramodh (Frontiers in Surgery, 2022)
Crohn’s disease of the small bowel could present as inflammatory or fibrotic structuring and penetrating disease or a combination of those. It is pertinent to differentiate the disease process as well as the extent to plan effective management. Currently a combination of medical and surgical therapy is accepted while the debate on superiority of the individual modality continues. In managing structuring disease, identification of the disease process through imaging plays a pivotal role since inflammatory strictures respond to anti TNF and biological agents while fibrotic strictures require endoscopic or surgical intervention. Recent evidence suggests a larger role for surgical excision, particularly in ileo-colic disease while a balance between disease clearance and bowel preservation has to be achieved. Several adaptations to the surgical technique such as wide mesenteric excision, side to side or Kono-S anastomosis and long term metronidazole therapy has come into practice while their absolute benefit is yet to be determined. Penetrating disease requires a broader multidisciplinary approach with particular focus on nutrition, skin care and intestinal failure management. Current guidance directs towards early surgical intervention for penetrating disease when feasible. Accurate preoperative imaging, medical management of active disease plus surgical decision-making based on experience and evidence plays a key role in success.